2011
DOI: 10.1186/1477-7517-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering high rates of unsafe injection equipment reuse in rural Cameroon: validation of a survey instrument that probes for specific misconceptions

Abstract: BackgroundUnsafe reuse of injection equipment in hospitals is an on-going threat to patient safety in many parts of Africa. The extent of this problem is difficult to measure. Standard WHO injection safety assessment protocols used in the 2003 national injection safety assessment in Cameroon are problematic because health workers often behave differently under the observation of visitors. The main objective of this study is to assess the extent of unsafe injection equipment reuse and potential for blood-borne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…This study further revealed that the barriers to injection safety practices were: None display of injection safety guidelines, inadequate supply of injection safety material and resources; this corresponds with the findings of Sudesh, et al, (2013), Okwen, et al, (2011), Onyemocho et al, (2013 and Gadzama et al( 2014) who documented that non-compliance with safe injection practices in health facilities was due lack of availability of equipment and resources for proper disposal, and none availability of injection safety guidelines. It should be appreciated that displayed guidelines will constantly remind practitioners and stimulate them to comply with safety practices.…”
Section: Discussionsupporting
confidence: 87%
“…This study further revealed that the barriers to injection safety practices were: None display of injection safety guidelines, inadequate supply of injection safety material and resources; this corresponds with the findings of Sudesh, et al, (2013), Okwen, et al, (2011), Onyemocho et al, (2013 and Gadzama et al( 2014) who documented that non-compliance with safe injection practices in health facilities was due lack of availability of equipment and resources for proper disposal, and none availability of injection safety guidelines. It should be appreciated that displayed guidelines will constantly remind practitioners and stimulate them to comply with safety practices.…”
Section: Discussionsupporting
confidence: 87%
“…The supervisors of injection practices reported that no stockouts of any standard disposable or safety syringes occurred during the last 6 months in 95.6% of the facilities. In Cameron, 44% of health workers at public hospitals reported reuse of injection equipment that could be partly explained by a shortage of syringes through review of injection equipment supply purchase records [14]. In Philippines, the frequency of reuse of needles and evidence for attempts to sterilize used needles was less than 16% [11].…”
Section: Discussionmentioning
confidence: 99%
“…HCV infections represent a serious and urgent public health problem in Africa where the prevalence is high, the cost of treatment is prohibitive, the reuse of improperly sterilized needles, transfusion of unscreened blood are common and resources to implement public health measures against its spread are limited [Madhava et al, 2002;Prati, 2006;Okwen et al, 2011;Averhoff et al, 2012;Harnois, 2012]. In this study, a prevalence of $3% of HCV infection (based on PCR detection of HCV RNA) was recorded among samples collected from pregnant women in 1995 from Côte d'Ivoire.…”
Section: Discussionmentioning
confidence: 92%